2017
DOI: 10.1038/npp.2017.64
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tryptophan Depletion on Executive System Function during Menopause is Moderated by Childhood Adversity

Abstract: Many healthy women with no history of cognitive dysfunction experience subjective executive difficulties during menopause. Preclinical literature suggests latent effects of early life adversity on serotonin function may play a role in this phenomenon. However, evidence in human participants regarding the mechanisms by which loss of estradiol contributes to this vulnerability is lacking. Here we examined the impact of tryptophan depletion (TD) and adverse childhood experiences (ACE) on brain activation during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 48 publications
(54 reference statements)
2
12
0
Order By: Relevance
“…While we hypothesized that TD would selectively impair connectivity in the high ACE group, we found that TD instead selectively improved connectivity in the high ACE group. Though contrary to our hypothesis, this result is consistent with previous findings demonstrating that tryptophan depletion attenuates ACE effects on dorsolateral prefrontal cortex activation during the n-back in menopausal women (Shanmugan et al, 2017a). That TD attenuated the negative effects of ACE on connectivity suggests that serotonergic differences may be contributing to baseline differences in functional connectivity between ACE groups.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…While we hypothesized that TD would selectively impair connectivity in the high ACE group, we found that TD instead selectively improved connectivity in the high ACE group. Though contrary to our hypothesis, this result is consistent with previous findings demonstrating that tryptophan depletion attenuates ACE effects on dorsolateral prefrontal cortex activation during the n-back in menopausal women (Shanmugan et al, 2017a). That TD attenuated the negative effects of ACE on connectivity suggests that serotonergic differences may be contributing to baseline differences in functional connectivity between ACE groups.…”
Section: Discussionsupporting
confidence: 83%
“…That TD attenuated the negative effects of ACE on connectivity suggests that serotonergic differences may be contributing to baseline differences in functional connectivity between ACE groups. Non-human primate (Shively et al, 2003) and human participant (Shanmugan et al, 2017a) studies have shown that estradiol attenuates the effects of early adversity on serotonin (Shively et al, 2003; Shanmugan et al, 2017a) and DLPFC function (Shanmugan et al, 2017a), suggesting estradiol may similarly attenuate the impact of ACE on connectivity observed in this study. Importantly, many women have contraindications to hormone therapy and results of this study suggest future research aimed at alleviating executive difficulties during menopause should examine serotonergic targets, particularly in the context of significant childhood adversity.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations